Analysis of Amylase, Protease, and Peroxidase Enzymes in Eco-Enzymes Based on Mango Peel, Pineapple, and Cabbage Using UV-Vis Spectrophotometry - Istika Listyana; Regina Tutik Padmaningrum (Universitas Negeri Yogyakarta, 2026)
Waste accumulation is dominated by organic waste, originating from food scraps, household waste, and commercial activities. This study aimed to examined the relationship between raw material composition and enzyme activity in eco-enzyme products using UV-Vis spectrophotometry. Eco-enzyme was produced from the fermentation of organic materials (pineapple peel, mango peel, and cabbage), molasses, and water with a mass ratio of 3:1:10, then fermented for 5 months. Qualitative tests to determine the presence or absence of amylase, protease, and peroxidase enzymes were carried out using the Benedict, Ninhydrin, and Addy Goodman methods. Quantitative tests were carried out using UV-Vis spectrophotometry to determine enzyme activity.The results showed that the eco-enzyme had an acidic pH (2.51-2.35) with a brown color and a sour aroma. The highest enzyme activities for amylase, protease, and peroxidase were found in composition 4 (3.86384 U/mL); composition 4 (3.27301 U/mL); and composition 2 (1,554.48 U/mL), respectively. Thus, the resulting eco-enzyme has potential as an enzyme source and can be applied in several fields.